Paradoxical upgrading reaction following treatment of disseminated tuberculosis-associated haemophagocytic lymphohistiocytosis in an infant without HIV: a case report and review of the literature. (3rd April 2022) - Chidambaram, Aakash Chandran; Maya, Malini; Sugumar, Kiruthiga; Parameswary, Singaravadivelu; Ramamoorthy, Jaikumar Govindaswamy; Selvan, Tamil
ABSTRACT: Tuberculosis-associated haemophagocytic lymphohistiocytosis (HLH) is rare in paediatrics and can be fatal if not recognised and treated on time. A 3-month-old infant with tuberculosis and HLH is described. He was successfully treated with anti-tuberculous therapy (ATT) which comprised isoniazid, rifampicin, pyrazinamide, ethambutol, streptomycin and dexamethasone (10 mg/m 2 /day). On Day 28 of therapy, he developed a paradoxical upgrading reaction to ATT for which he was again treated with (oral) corticosteroids for 4 weeks. He recovered successfully and is now completely well and asymptomatic. To the best of our knowledge, this is the first case of a child having a paradoxical upgrading reaction following treatment for TB-HLH. Abbreviations ATT: anti-tuberculous therapy; CB-NAAT: cartridge-based nucleic acid amplification test; CECT: contrast-enhanced computed tomography; HLH: haemophagocytic lymphohistiocytosis; NK: natural killer, PUR: paradoxical upgrading reaction; sHLH: secondary HLH.